2000
DOI: 10.1021/bi001070l
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Delta Subunit to Rod Phosphodiesterase Catalytic Subunits Requires Methylated, Prenylated C-Termini of the Catalytic Subunits

Abstract: PDE6 (type 6 phosphodiesterase) from rod outer segments consists of two types of catalytic subunits, alpha and beta; two inhibitory gamma subunits; and one or more delta subunits found only on the soluble form of the enzyme. About 70% of the phosphodiesterase activity found in rod outer segments is membrane-bound, and is thought to be anchored to the membrane through C-terminal prenyl groups. The recombinant delta subunit has been shown to solubilize the membrane-bound form of the enzyme. This paper describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…The slow lateral diffusion and the absence of any significant interdisc transfer of EGFP-PDE6C both indicate that it is predominantly membranebound in Xenopus rods. This notion differs from the hypothesized existence of soluble PDE6 in photoreceptor cells (36,37). The hypothesis is based on the observation that upon extraction from bovine retina, a significant fraction of PDE6 is found in a soluble complex with the 17-kDa prenyl-binding protein PrBP/␦, also known as the ␦-subunit of PDE6 (36).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The slow lateral diffusion and the absence of any significant interdisc transfer of EGFP-PDE6C both indicate that it is predominantly membranebound in Xenopus rods. This notion differs from the hypothesized existence of soluble PDE6 in photoreceptor cells (36,37). The hypothesis is based on the observation that upon extraction from bovine retina, a significant fraction of PDE6 is found in a soluble complex with the 17-kDa prenyl-binding protein PrBP/␦, also known as the ␦-subunit of PDE6 (36).…”
Section: Discussionmentioning
confidence: 98%
“…The hypothesis is based on the observation that upon extraction from bovine retina, a significant fraction of PDE6 is found in a soluble complex with the 17-kDa prenyl-binding protein PrBP/␦, also known as the ␦-subunit of PDE6 (36). PrBP/␦ was shown to interact with the methylated prenylated C termini of PDE6A and PDE6B and solubilize the enzyme from the membrane in vitro (37). However, immunohistochemical analysis has shown that PrBP/␦ localizes to the IS or near the RIS/ROS junction and does not co-localize with PDE6 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a large repertoire of prenyl proteins, such as subunits of PDE6, GRK1, GRK7, Rab13, Rap1a, Rap2b, RhoA, RhoB, Rnd1, Rap2c, RasD2, and Reb-L1, bind to PDEδ (20,22,27,(31)(32)(33). Among RAS proteins, in addition to KRAS4b, NRAS and HRAS have also been shown to bind to PDEδ (20,27).…”
Section: Identification Of a Conserved Sequence Motif In Kras4b And Imentioning
confidence: 99%
“…The 17-kDa prenyl-binding protein (PrBP/␦), originally described as the ␦-subunit of PDE6 (33), is able to solubilize membrane-associated rod PDE6 in vitro (23,34) by binding to the hydrophobic prenyl groups attached to the C termini of the PDE6 catalytic subunits (35). Because hydrophobic interactions may stabilize GARP2-PDE6 interactions (see previous section), we wondered whether PrBP/␦ binding to PDE6 would solubilize the enzyme as a complex with GARP2 or, alternatively, compete with GARP2 for binding to a hydrophobic region on PDE6.…”
Section: The 17-kda Prenyl-binding Protein (Prbp/␦) Releases Pde6 Bumentioning
confidence: 99%